Redefining Quranic Health Terminology in the Digital Sphere: The Medicalization of Scriptural Ethics in Institutional Medical Discourse in Indonesia - Mahbub Ghozali; Chandra Kartika Dewi; Khamim Khamim (Al-Qudwah, 2026)
This study aims to analyze the mechanisms underlying the medicalization of Quranic ethics within digital health discourse by examining how medical institutions position the sacred text as a semiotic infrastructure and a tool for moral legitimization on Instagram. This phenomenon reflects a shift in the function of the Quran—from an eschatological-narmative guide to an affective technology serving the interests of medical corporate authorities. Employing a qualitative approach with a case study design, this research conducts digital observations of Instagram posts by healthcare institutions in Indonesia. These institutions were purposively selected based on their consistent use of Quranic verses as tools for health communication. The findings reveal that medicalization occurs throught the decontextualization of verses from their classical theological meanings and their reorientation toward practical clinical functionalization. The study identifies three key mechanisms in this process. First, the re-ontologization of the text, which transforms Quranic verses into dynamic performances of mental and physical health. Second, the functionalization of authority, which mobilizes verses as a “sacred shortcut” to legitimize clinical narratives and preventive actions. Third, the construction of associative identity, which converts the universal ethics of the Quran into symbolic capital through religious imagery. This study concludes that, within digital health institutions, the Quran has become a new epistemic site where revalation attains functional and clinical validity. The implication is that religious authority in the digital space no longer depends solely on the depth of theological hermeneutics but also on the capacity for visual aestheticization to mediate texts that engage the affective dimensions of modern audiences.